Outcomes of acute meningitis according to immunosuppression status: 15-year retrospective cohort - Carla Marina Román-Montes; Valeria Alejandra Pérez-López; Nayeli Esmeralda Avalos-Celis; Aranza Castillejos-Gracia; Alfredo Ponce de León; Guillermo Arturo Guaracha-Basañez (PLoS ONE, 2026)
Acute meningitis remains a primary global health concern. Immunosuppressed patients have risks due to atypical clinical presentations and a broader range of causative pathogens. We aimed to describe the outcomes and clinical features of acute meningitis according to immunosuppression status. We performed a retrospective cohort study of adults with acute meningitis from January 2009 to December 2023. Patients with postsurgical meningitis were excluded. Outcomes and demographic, clinical, and laboratory features were compared using non-parametric statistical tests, and mortality was analyzed using multivariate logistic regression. Among 189 patients, 96 (51%) were immunosuppressed. The median age was lower in immunosuppressed patients (36 vs. 50 years, p < 0.01). There were no differences in symptoms; the classical triad was present in only 21% vs. 19%. Immunosuppressed patients had lower CSF glucose levels (59% vs. 39%, p = 0.004). Overall mortality was 20%, with no significant difference by immune status. Independent predictors of death included age over 50 years (OR 2.9), altered mental status (OR 4.7), and bacterial meningitis (OR 2.3). Acute meningitis in immunosuppressed hosts shows attenuated inflammatory CSF profiles and a broader etiologic spectrum. Immunosuppression was not independently associated with in-hospital mortality.